Characterization of Karst Features in the Mishrif Formation (Zubair Field): Integrating Petrographic, Stratigraphic, and Tectonic Analysis for Reservoir Quality Assessment - Al-Janaby, Muhaimen Mutar; Al-Najm, Fahad M.; Almayahi, Ali Z. (International Journal of Aquatic Research and Environmental Studies, 2026)
The Mishrif Formation in the Zubair Oil Field of south Iraq is a very complex carbonate ramp reservoir of mid Cretaceous (Cenomanian–Early Turonian) age. In addition to primary depositional conditions, meteoric karstification resulting from subaerial exposure events has the greatest control on reservoir quality. This study combines thin-section petrography, facies determinism, sequence stratigraphy and tectonic controls to describe the genesis of secondary karstic porosity and its effects on reservoir quality. Secondary pore types were identified and classified by vacuum-impregnation with blue-dyed epoxy for samples taken from a key well suite (ZB-40, ZB-43, ZB-47, ZB-49, ZB-114, ZB-195 and ZB-199). Results indicate that meteoric karstification is facies selective and very deterministic. The high energy and grain supported and framework-supported facies (shoal grainstones, rudist rudstones and boundstones) were highly unstable aragonitic bioclasts (rudists and bivalves) that served as extremely "reactive" "reactor beds. These facies experienced a high degree of dissolution, resulting in many coalescent vugs, "megamolds" and channel networks (karst "super-highways" with porosity in excess of 25-35% and permeabilities in excess of 100 to 1000 mD). Mixed grain-matrix packstones are moderately karstified (porosity is 14-25%, and permeability is 1-50 mD), and are characterized by moderate, but patchy, karst enhancement with the tectonic fractures serving as "super connectors" between isolated moldic pores. Mud-supported mudstones and wackestones are low permeability aquitards and baffles (porosity < 5%, permeability < 0.1 mD), dissolution only occurs on tight local fracture pathways. Major 3rd order sequence boundaries are periods of extended subaerial exposure, which lead to deep and significant karst overprints; maximum flooding surfaces are intra-reservoir seals. The four anticlinal domes (Hammar, Shuaiba, Rafdhia, and Safwan) developed during the depositional period creating bathymetric paleo highs that led to rudist shoal deposition and prolonged subaerial exposure. The extensive fracture networks formed by tectonic compression were essential to the vertical plumbing system needed to get the aggressive meteoric fluids into the formation. This integrated multi scale model is a powerful predictive model to map reservoir quality and identify "sweet" spots and drilling hazards in uncored portions of the Zubair Field.